Niko Zupanič v Etnografskem muzeju v Beogradu - Bižić Omčikus, Vesna (Etnolog. Nova vrsta (Ljubljana), 2003)
The article presents documents from the archives of the Ethnographic Museum in Belgrade which witness to the activities of Niko Zupanič as curator of the museum`s Anthropology and Palaeontology Department from 1914 to 1920, and to his later efforts to lay down the anthropological criteria for the operation of the Ethnographic Institute, which was established in Ljubljana in 1921.
Keywords: Županič, Niko, 1876-1961; Etnografski muzej; Belgrade; Beograd; etnologija; ethnology; fizična antropologija; biografije